A Critical Review of Overheating Risk Assessment Criteria in International and National Regulations—Gaps and Suggestions for Improvements - Mahsan Sadeghi; Dong Chen; Anthony Wright (Energies)
The escalating environmental threat of indoor overheating, exacerbated by global climate change, urbanisation, and population growth, poses a severe risk to public health worldwide, specifically to those regions which are exposed to extreme heat events, such as Australia. This study delves into the critical issue of overheating within residential buildings, examining the existing state of knowledge on overheating criteria and reviewing overheating guidelines embedded in (a) international standards and (b) national building codes. Each regulatory document is analysed based on its underlying thermal comfort model, metric, and indices. The advantages and limitations of each document are practically discussed and for each legislative document and standard, and the quantitative measures have been reviewed, analysed, and summarised. The findings illuminate a global reliance on simplistic indices, such as indoor air temperature and operative temperature, in the existing regulatory documents. However, other critical environmental parameters, such as relative humidity, indoor air velocity, and physiological parameters including metabolic heat production and clothing insulation, are often not included. The absence of mandatory regulations for overheating criteria in residential buildings in some countries, such as in Australian homes, prompts the call for a holistic approach based on a thermal index inclusive of relevant environmental and physiological parameters to quantify heat stress exposure based on human thermal regulation. Gaps and limitations within existing guidelines are identified, and recommendations are proposed to strengthen the regulatory framework for overheating risk assessment in residential buildings. The findings hold significance for policymakers, building energy assessors, architects, and public health professionals, providing direction for the improvement of existing, and development of new, guidelines that aim to enhance indoor thermal condition and population health while ensuring energy efficiency and sustainability in the building stock.